The Transformation of Religious Communication: An Analysis of Opportunities, Challenges, and Strategies for Maintaining the Credibility of Religious Leaders - Indah Rahmawati; Ilyas Mulyana; Dadang Kuswana (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2026)
The transformation of digital technology has brought significant changes in the way religious communication takes place in society. The development of social media, video platforms, and various communication apps has created new spaces for spreading religious messages while also changing the relationship between religious leaders and their audience. These changes present various opportunities to expand the reach of religious communication, but they also bring challenges related to the authority and credibility of religious leaders in the digital space. This study aims to analyze the opportunities arising from the transformation of religious communication in the digital era, identify the challenges faced by religious leaders in maintaining their credibility, and formulate strategies to strengthen that credibility. The research uses a descriptive qualitative approach with a literature study method. The research shows that the transformation of religious communication opens up opportunities, such as expanding the reach of preaching, forming virtual religious communities, and strengthening more participatory religious interactions. However, religious leaders face challenges like the democratization of religious authority, digital misinformation, and demands for public authenticity. Therefore, strengthening digital literacy, transparent communication, and cross-disciplinary collaboration are important strategies to maintain the credibility of religious leaders in the digital era.